STUDENTS PERCEPTION: THE USE OF GOOGLE CLASSROOM IN TEACHING-LEARNING PROCESS - Manda Negara, Irma (Jurnal Ilmiah Spectral, 2018)
The purpose of this study was to determine the perceptions of students regarding the use of Google Classroom in learning activities. The subject of this study is the seventh-semester students as many as 54 students of English Literature Study Program at STBA Pontianak. The results were described using descriptive statistics, the average of students gives a positive response. For the usefulness indicator the results indicated that, the highest is Google Classroom is very useful for learning (88.51%) in the excellent category, the middle is Google Classroom makes learning effective (80.37%) in the excellent category, and the lowest is Google Classroom can improves student performances and increases student activity 70% was included in the good category. For the Google Classroom ease of use indicator the results indicated that, the highest is Google Classroom easy to use (91.85%) in the excellent category, the middle is Google Classroom easy to learn (91.48%) in the excellent category, and the lowest is Google Classroom makes learning flexible and helpful in the learning process (77.4%) was included in the good category. For the indicator of satisfaction the results indicated that, the highest is Students can use the Google Classroom according to what they want (92.60%) in the excellent category, the middle is the application is amazing (91.11%) in the excellent category, and the lowest is Google Classroom convenient and comfortable to use (87.40%) in the excellent category.